2012
DOI: 10.1007/s10725-012-9664-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of betaine improves solution uptake and in vitro shoot multiplication in tea

Abstract: The application of betaine, a quaternary ammonium compound influenced the micropropagation in two commercially important UPASI (U-9 and U-10) cultivars of tea. Growth and multiplication of shoots of both the cultivars was enhanced significantly in the presence of 125-1,000 mg l -1 betaine with best response at 1,000 mg l -1 betaine. The shoots turned brown and died within 15 days when 1,500 mg l -1 betaine was applied. The study showed faster water/nutrient uptake in the presence of betaine. Higher assimilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…among king oyster mushroom . A decrease in carbohydrate concentration might be due to the increase in nitrate reductase activity by GB application . There was no significant effect of GB enriched cotton waste on crude fiber and ash (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…among king oyster mushroom . A decrease in carbohydrate concentration might be due to the increase in nitrate reductase activity by GB application . There was no significant effect of GB enriched cotton waste on crude fiber and ash (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…2 A decrease in carbohydrate concentration might be due to the increase in nitrate reductase activity by GB application. 36 There was no significant effect of GB enriched cotton waste on crude fiber and ash (Table 3). These findings regarding crude fiber and ash are in accordance with the results of Krüzselyi et al 2 The effect of different concentrations of GB enriched cotton waste on Zn, Cu, Mg, Mn, Na, Fe and Ca of fruiting body of king oyster mushroom was significant ( Table 3).…”
Section: Crude Protein Carbohydrates Crude Fibers Ash and Fats Conmentioning
confidence: 92%
“…Therefore, based on other studies (Gibon and Larher, 1997;Korkmaz et al, 2012), we concluded that GB is not an osmolyte, as reported by Asma et al (2006), who observed that the foliar application of GB to corn did not have the expected effect. Although it has been reported that GB acts as an osmoprotectant in some plant species, it is important to mention that these studies have only been performed in vitro (Saini et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In S. raeseri Boiss & Heldr., the 100 mg/l GB + 0.5 mg/l NAA combination treatment appears suitable for the in vitro shoot proliferation stage (5.5 shoots/explant 2.34 cm long and 75% shoot multiplication percentage). Saini et al [24] reported the stimulatory effect of 125-1,000 mg/l GB on growth, shoot number and shoot multiplication rate in two commercially important UPASI (U-9 and U-10) cultivars of tea (Camellia sinensis L. (O.)…”
Section: Ex Vitro Acclimatization Of In Vitro Rooted Plantletsmentioning
confidence: 99%